Values and communication in modern Ukraine: to the topic of correlation: Цінності та комунікація в сучасній Україні: до питання взаємозв’язку - Hryshchuk, Viktor; Hryshchuk, Oksana; Tokarska, Antonina (Przegląd Wschodnioeuropejski, 2020)
The article is focused on values of being, which are realized through means of communication, formed on the basis of value rationalization. At the same time the communication makes its own influence on formation and functioning of values in a society. The theoretical and the practical in a classic relation of values and communication is marked by reorientation of the priorities through crisis conditions of contemporary being: the sphere of practical prevails over the theoretical. Eastern European area of values demonstrates both the best examples of values in the weltanschauung, and those that are unacceptable for localized communities. The authors do not judge behavioral and cognitive archetypes, arguing instead in favour of the reborn values, included in a holistic European value model, as well as adoption of new meanings of the rapidly changing contemporary environment, with a view of its moderation in the name of the good and the being.